Effects of Ethnicity and Sex on the Pharmacokinetics and Pharmacodynamics of the Selective Sphingosine-1-Phosphate Receptor 1 Modulator Ponesimod: A Clinical Study in Japanese and Caucasian Subjects - Reyes, Maribel; Hoch, Matthias; Brossard, Patrick; Dingemanse, Jasper (Pharmacology, 2014)
The aim of this study was to evaluate the relative pharmacokinetic (PK) and pharmacodynamic (PD) properties of a single dose of ponesimod, an oral and selective sphingosine-1-phosphate receptor 1 (S1P 1 ) modulator, in Japanese and Caucasian healthy subjects and explore the effects of sex on PK. Subjects received a single 40-mg dose of ponesimod in a single-centre, open-label, parallel-group study design. Ten Japanese and 10 Caucasian healthy subjects (age: 22-45 years, 1:1 sex ratio) participated in the study and were matched for body weight (w10%). Ponesimod concentration in plasma was determined by liquid chromatography tandem mass spectrometry, and PK parameters were obtained by non-compartmental analysis. Total lymphocyte count served as PD marker. Adverse events (AEs), laboratory values, electrocardiography (12-lead ECG), and vital signs were assessed for safety and tolerability. Administration of ponesimod resulted in similar PK parameters between the two ethnic groups, with a 16% higher exposure [AUC 0- ∞ of 7,368 ng · h/ml (95% CI: 6,059-8,962) vs. 6,353 ng · h/ml (4,950-8,154)] and a 17% longer terminal elimination half-life [32.9 h (30.1-36.0) vs. 28.1 h (23.4-33.6)] in Japanese compared to Caucasian subjects. Exposure was slightly higher in female subjects [7,488 ng · h/ml (5,983-9,371)] than in male subjects [6,252 ng · h/ml (5,031-7,771)]. The maximum mean lymphocyte count decrease from baseline, observed 6 h after receiving the dose in both groups, was similar in Japanese subjects (61.8%) and Caucasians (62.5%). The maximum mean heart rate (ECG) reduction from baseline was similar, with a difference of 4.2 bpm between Caucasian and Japanese subjects, observed 2.5 h after receiving the dose in both ethnic groups. There were no clinically relevant changes in other safety variables. No serious AEs were reported during the study. This study showed that the PK and PD profile of ponesimod was similar in Japanese and Caucasian subjects. No unexpected safety findings were reported. No dose adjustment is deemed necessary for Japanese subjects compared to Caucasians. i 2014 S. Karger AG, Basel